2007
DOI: 10.1590/s1678-77572007000100015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tangential and normal components of oral forces

Abstract: Oral forces applied to human teeth during biting and mastication are normally described in the literature only in terms of their axial components. The purpose of this study was to fully determine the spatial characteristics of the oral resultant force – its normal and tangential components - for a given individual. A load cell was especially manufactured to measure oral force and was temporarily implanted as a prosthetic device in the dental arch of a volunteer, replacing his missing upper first molar. The mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…For F load = 4 mN/m (assuming that the coated surfaces have approximately the same E and ν as bare mica and silica) the pressure ( P ) is about 40 MPa in absence of adhesion and 19 MPa for the system having the largest adhesion. These pressures are of the same magnitude as the pressures exerted on teeth during chewing [46], and an order of magnitude higher than in human joints [47].…”
Section: Friction Between Adsorbed Polymer Layersmentioning
confidence: 76%
“…For F load = 4 mN/m (assuming that the coated surfaces have approximately the same E and ν as bare mica and silica) the pressure ( P ) is about 40 MPa in absence of adhesion and 19 MPa for the system having the largest adhesion. These pressures are of the same magnitude as the pressures exerted on teeth during chewing [46], and an order of magnitude higher than in human joints [47].…”
Section: Friction Between Adsorbed Polymer Layersmentioning
confidence: 76%
“…It has been found that the produced force of a human is approximately 40 N during swallowing; 170–881 N during chewing nuts, and 39–788 N for corresponding mastication loads. In addition, this amount of force increases to optimum range from 200-540 N in the posterior (molar) region 5 , 18 , 24 . Therefore, these materials may not be able to withstand extreme occlusal forces in the oral environment.…”
Section: Discussionmentioning
confidence: 97%
“…The breakdown of food in the mouth begins with mastication, which contributes to physical forces generated by the occlusion of the teeth that change over time, of which maximum value can range from 39 to 800 N, depending on the food type (de Las Casas et al., 2007). Mastication drives the breakdown of the macroscopic structure of ingested solid food by the crushing and shearing action of the teeth to form a masticated mass, known as a food bolus (Brownlee et al., 2018).…”
Section: Digestive Organs That Contribute To Structural Breakdown Of Solid Starch‐based Foodsmentioning
confidence: 99%